Al-Tayyārāt al-Dīniyyat al-Mutaṭarrifat wa ‘Istiqṭāb al-Shabāb: Dirāsat Ḥālat Lībiyā: [Waves of Religious Extremism and the Polarization of Youth: A Case Study of Libya] - Baddah, Laylay Alfaytouri Abdussalam (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2022)
The study dealt with extremist religious currents to attract young people into Libyan society through the framework of functional analysis, which resulted in the presence of dysfunction in society. This study sheds light on the relationship between Libyan youth and religious extremism in the context of the Arab Spring, meaning the political transition after the fall of Muammar Gaddafi’s regime in 2011. Some trends are undergoing changes, resulting in the emergence of extremist religious currents. It can be concluded from this study that the problem of extremism is due to the existence of a cultural conflict and a cultural gap between two generations. This gap is the reason for creating the psychological, intellectual, political and ideological divergence of the young generation from the adult generation.